G403 Assessing the value of bone marrow aspirate and trephine in identifying metastatic involvement in children with ewing's sarcoma: a retrospective single centre experience. (27th April 2015) - Dandapani, M; Hobin, D
Abstract : Background: Bilateral Bone marrow aspirates and trephines are part of the initial staging evaluation of patients with Ewing's sarcoma. However, the utility of performing this invasive investigation in addition to imaging with MRI and Technetium 99 bone scan has not been assessed. Aim: To assess the value of performing bone marrow aspirates and trephines in identifying metastases when compared to imaging, particularly Technitium 99 bone scan. Methods: Retrospective review of 48 children aged 16 and under with Ewing's sarcoma treated in our institution over a 14 year period (August 2000–September 2014). Results: The demographic details of our patients were as follows- we treated 25 males and 23 females (M:F = 1.08:1). 54% of patients were over 10 years old while 12.5% of patients were under 5 years old; the remaining 33.3% were aged between 5 and 10 years. Using imaging alone, 69% had localised disease while 31% had metastatic disease. 81% of patients (n = 39) had bone marrow aspirates and trephines performed, of which 3 were positive for disease; one of these patients had a pelvic primary and the marrow was positive on the left side which was the location of the primary site. 43 patients (90%) had a bone scan, of which 10 were positive for bony metastases. All three patients who had bone marrow positivity also had metastatic lesions on bone scan. 4 patients with metastatic bony lesions did not have a bone marrow performed, while the other 3 did not have evidence of disease in the bone marrow aspirate or trephine. Conclusions: Although our numbers are small, there is a high correlation between bony metastases identified by Technetium 99 bone scan and bone marrow aspirate and trephine positivity. Further prospective evaluation is required to determine whether a bone marrow examination adds any value to the initial staging of Ewings sarcoma over currently available imaging techniques and whether it can be omitted from the list of initial staging assessments.